Poly(sodium acrylate) hydrogels: synthesis of various network architectures, local molecular dynamics, salt partitioning, desalination and simulation. Issue 48 (21st November 2019) - Arens, Lukas; Barther, Dennis; Landsgesell, Jonas; Holm, Christian; Wilhelm, Manfred
Abstract : The effect of network architecture on salt partitioning between gel and supernatant phases is investgated and used to desalinate NaCl solutions. Abstract : Various poly(sodium acrylate) hydrogels with different architectures, such as single networks, interpenetrating double networks and surface crosslinked hydrogels, are synthesized with a systematic change in their degree of crosslinking. The influence of these 3D structures on the absorbency of aqueous NaCl solutions is investigated. The local polymer mobility in water is probed in the form of transverse ( T 2 ) 1 H-relaxation at a low field, which allowed confirming the structural aspects of the studied network topologies. Salt partitioning between the gel and the surrounding solution phase in NaCl solutions with an initial salt concentration of c 0 = 0.017–0.60 mol L −1 (≙1–35 g L −1 ) is investigated. The data are compared with an idealized mean-field Donnan model, which fit the experimental findings only under the assumption of a drastically reduced effective charge density of f eff ≈ 25 mol% independent of the hydrogel used. The unequal salt distribution allows desalination of salt water by applying an external pressure to a swollen hydrogel to recover its water which has a lower salinity. The specific energy needed to desalinate 1 m 3 was estimated to be 6–18 kW h m −3 . This value decreases with a lower degree of swelling independent of the network topology. Besides the experiments, simulations based on a Poisson–Boltzmann mean-field model and MD simulations are performed to determine the degree of swelling and salt partitioning as a function of c 0 for different hydrogels. Both simulations describe qualitatively the experimental data, where deviations can be ascribed to model simplifications and the imperfect structure of the hydrogels synthesized via free radical polymerization.